A population-based longitudinal study of childhood neurodevelopmental disorders, IQ and subsequent risk of psychotic experiences in adolescence. Issue 15 (November 2014) - Khandaker, G. M.; Stochl, J.; Zammit, S.; Lewis, G.; Jones, P. B.
<x content-type="archive" xml:space="preserve">Abstract</x> Background. Schizophrenia has a neurodevelopmental component to its origin, and may share overlapping pathogenic mechanisms with childhood neurodevelopmental disorders (NDs). Nevertheless, longitudinal studies of psychotic outcomes among individuals with NDs are limited. We report a population-based prospective study of six common childhood NDs, subsequent neurocognitive performance and the risk of psychotic experiences (PEs) in early adolescence. Method. PEs were assessed by semi-structured interviews at age 13 years. IQ and working memory were measured between ages 9 and 11 years. The presence of six NDs (autism spectrum, dyslexia, dyspraxia, dysgraphia, dysorthographia, dyscalculia) was determined from parent-completed questionnaires at age 9 years. Linear regression calculated the mean difference in cognitive scores between children with and without NDs. Associations between NDs and PEs were expressed as odds ratios (ORs) with 95% confidence intervals (CIs); effects of cognitive deficits were examined. Potential confounders included age, gender, father's social class, ethnicity and maternal education. Results. Out of 8220 children, 487 (5.9%) were reported to have NDs at age 9 years. Children with, compared with those without, NDs performed worse on all cognitive measures; the adjusted mean difference in total IQ was 6.84 (95% CI 5.00–8.69). The association between total IQ and NDs was linear (p < 0.0001). The risk of PEs was higher in those with, compared with those without, NDs; the adjusted OR for definite PEs was 1.76 (95% CI 1.11–2.79). IQ (but not working memory) deficit partly explained this association. Conclusions. Higher risk of PEs in early adolescence among individuals with childhood ND is consistent with the neurodevelopmental hypothesis of schizophrenia.